Robin George Collingwood: artistic taste as a factor of art history personalization - Ternova, Maryna (Ukrainian Cultural Studies, 2022)
The article considers ’artistic taste’ both as a theoretical problem that is actively involved in the space of European art history at the turn of XVII – XVIII centuries, and as a manifestation of the personal preferences of artists whose place in the hierarchy of creative importance took into account such factor as artistic taste. The specificity of ’aesthetic taste’ as a theoretical problem and as a personal assessment of works of art, which has its own place in modern humanities, is highlighted. It is shown that in the second half of the XX century, the tendency to analyze taste as an aesthetic and artistic phenomenon was outlined in the theoretical aspect. The standpoint of R.G. Collingwood, a famous English philosopher, aesthetician, art critic and historian of science, who attributed ’taste’ to the cornerstones of aesthetic and artistic concepts, is highlighted, at the same time emphasizing the meaning of taste as a manifestation of the artist professional culture. It is argued that the actualization of the theoretical views of R.G. Collingwood is important in terms of the use of the interdisciplinary approach by modern cultural studies, which appeared in English humanism in general, and in the standpoint of the author of monograph ’The Principles of Art’. R.G. Collingwood’s attitude to the historical and philosophical, aesthetic and artistic tradition of understanding of the ’taste’ has been analyzed and the differences that took place in the interpretation of the ’taste’ in the logic of the formation of both aesthetic and artistic approaches are emphasized. The concept of ’taste’ is an integral part of the aesthetic and art theory, while preserving the ’artistic’ aspect for the evaluation of works of art, as well as the ’aesthetic’ aspect, when it comes to non-artistic space, for the evaluation of which the interaction with the entire ’sensual’ human nature is necessary: from ’senses’ that form ’base’ aesthetics (senses of vision, hearing, touch, odor), to ’feelings’, for example, sense of beauty, sublime, tragedy, shame. The group of artists whose work allows to ’illustrate’ their personal preferences and conceptualize a number of issues related to the use of the theoretical and practical potential of existing modifications of ’artistic taste’ is outlined.